Exploring microenvironmental configuration effects of Cu-based catalysts on nitrate electrocatalytic reduction selectivity - Long, Xianhu; Zhong, Tao; Huang, Fan; Li, Ping; Zhao, Huinan; Fang, Jingyun; Shu, Dong; He, Chun (Applied catalysis. B, Environmental, 2025)
The reduction of nitrate (NO3−) can mitigate its impact on the environment. The electrochemical NO3− reduction reaction (NO3RR) offers a green and environmentally friendly approach for sustainable ammonia (NH3) synthesis, yet hindered by the complex reaction pathways. Herein, for the first time, we regulated the atomic structure of Cu-based catalysts to control the product selectivity of the NO3RR, and three catalysts with different microenvironmental configurations were successfully synthesized. Cu nanocluster (Cu NC) exhibited state-of-the-art NH3 selectivity (81.1 %), while Cu diatom (Cu DAC) was inclined to produce N2 (93.4 %), and Cu single atom (Cu SAC) was more likely to simultaneously produce both NH3 (44.9 %) and N2 (51.9 %). A series of experiments and theoretical calculations were performed to unveil the underlying mechanism. It was found that Cu NC can form Cu-O bonds with multiple oxygen atoms of the NO3−, facilitating electron transfer and rapid NH3 synthesis. Cu DAC was more conducive to the formation of N*intermediate, which is crucial for N2 production. This work provides a novel paradigm to regulate the NO3RR pathway and steer product selectivity via the microenvironmental configuration modulation of the electrocatalyst at the molecular level. [Display omitted] •Three Cu-based catalysts with different microenvironmental configuration were designed.•The functional properties of catalysts were revealed, each producing different reduction products.•The electrocatalytic characteristics of catalysts were analyzed through electrochemical analyses.•The reduction mechanisms of catalysts were explored using theoretical calculations.